USING THE TWO-TIER MULTIPLE CHOICE QUESTION TO PROMOTE SENIOR HIGH SCHOOL STUDENTS' READING COMPREHENSION - Wiwit Melayu; Don Narius (Journal of English Language Teaching, 2016)
This paper explains about the use of the two-tier mutliple choice question to promote senior high school students' reading comprehension. This model of assessment is modification of the traditional multiple choice question. If the traditional multiple choice question provides a question with some optional answers, distracters, the two-tier multiple choice question' model provide an additional question. This additional question is asked about the reason why answering the previous question. This model is aimed to set up the students to be struggling readers. It is also used to measure students' comprehension in comprehend the text. It can be seen from the reason of the students.